Role of treatment in the appearance and selection of BCR-ABL1 kinase domain mutations - Razga, Filip; Jurcek, Tomas; Zackova, Daniela; Dvorakova, Dana; Toskova, Martina; Jeziskova, Ivana; Mayer, Jiri; Racil, Zdenek (Molecular diagnosis & therapy, 2012)
BACKGROUND AND OBJECTIVE: The availability of different tyrosine kinase inhibitors (TKIs) with distinct anti-leukemic potency enables optimization of current therapeutic regimens; however, some patients lose their therapy response and acquire TKI resistance. In this study, we describe a single-center experience of monitoring BCR-ABL1 kinase domain (KD) mutations and discuss the impact of treatment on mutation selection. METHODS: Chronic myelogenous leukemia (CML) patients treated with TKIs at the Department of Internal Medicine-Hematology and Oncology, Masaryk University and University Hospital Brno during 2003-2011 were included in this study. A total number of 100 patients who did not achieve an optimal therapy response or who lost their therapy response were screened for the presence of BCR-ABL1 KD mutations, using direct sequencing. RESULTS: Our data show that pretreatment with non-specific non-TKI drugs prior to TKI therapy does not preferentially select for initial BCR-ABL1 KD mutations, in contrast to first-line imatinib therapy, which shows a clear predominance of T315I or P-loop mutations compared with mutations located in other KD regions. In addition, the median time to detection of P-loop mutations was substantially shorter in patients treated with first-line imatinib than in those pretreated with non-TKI drugs. Furthermore, analysis of CML patients who had recurrent resistance to TKI therapy revealed possible therapy-driven selection of BCR-ABL1 KD mutations. Finally, we confirm the previously described poor prognosis of CML patients with mutations in the BCR-ABL1 KD, since 40.0% of our CML patients who harbored a BCR-ABL1 KD mutation died from CML while receiving TKI treatment. Moreover, among the patients who are still on treatment, 27.8% have already progressed. Our data also confirm the unique position of the T315I mutation with respect to its strong resistance to currently approved TKIs. CONCLUSION: On the basis of the 'real-life' data described in this study, it is possible that the therapy itself results in its failure and selects the most resistant mutations under the selective pressure of the applied therapy regimen in some CML patients who harbor BCR-ABL1 KD mutations.
Keywords: mutace; dospělí; Female; inhibitory proteinkinas; Adult; ženské pohlaví; bcr-abl fúzní proteiny; lidé; chronická myeloidní leukemie; Antineoplastic Agents; protinádorové látky; Mutation; Male; Protein Kinase Inhibitors; Aged; lidé středního věku; senioři; mužské pohlaví; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Fusion Proteins, bcr-abl; Protein-Tyrosine Kinases; Middle Aged; tyrosinkinasy; Humans